De novo mutations in Caudal Type Homeo Box transcription Factor 2 (CDX2) in patients with persistent cloaca. (21st November 2017) - Hsu, Jacob S J; So, Manting; Tang, Clara S M; Karim, Anwarul; Porsch, Robert M; Wong, Carol; Yu, Michelle; Yeung, Fanny; Xia, Huimin; Zhang, Ruizhong; Cherny, Stacey S; Chung, Patrick H Y; et al.
Abstract: The cloaca is an embryonic cavity that is divided into the urogenital sinus and rectum upon differentiation of the cloacal epithelium triggered by tissue-specific transcription factors including CDX2 . Defective differentiation leads to persistent cloaca in humans (PC), a phenotype recapitulated in Cdx2 mutant mice. PC is linked to hypo/hyper-vitaminosis A. Although no gene has ever been identified, there is a strong evidence for a genetic contribution to PC. We applied whole-exome sequencing and copy-number-variants analyses to 21 PC patients and their unaffected parents. The damaging p.Cys132* and p.Arg237His de novo CDX2 variants were identified in two patients. These variants altered the expression of CYP26A1, a direct CDX2 target encoding the major retinoic acid (RA)-degrading enzyme . Other RA genes, including the RA-receptor alpha, were also mutated. Genes governing the development of cloaca-derived structures were recurrently mutated and over-represented in the basement-membrane components set ( q -value < 1.65 × 10 −6 ). Joint analysis of the patients' profile highlighted the extracellular matrix–receptor interaction pathway (MsigDBID: M7098, FDR: q -value < 7.16 × 10 −9 ). This is the first evidence that PC is genetic, with genes involved in the RA metabolism at the lead. Given the CDX2 de novo variants and the role of RA, our observations could potentiate preventive measures. For the first time, a gene recapitulating PC in mouse models is found mutated in humans.